Analisis Pemberian Insentif Dalam Upaya Meningkatkan Motivasi Kinerja Karyawan - Yusup, Yusup; Adhafiya, Wahyu (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2025)
This study aims to analyze the influence of motivation and compensation on employee performance at Singular Digital Printing Surabaya. The object of this study is Singular Digital Printing employees, with a population consisting of 60 employees. Due to the limited population, all employees with various statuses are used as samples with a saturated sampling technique. This study uses the Structural Equation Modeling (SEM) data analysis technique. Overall, the relationship in the analysis, namely incentives on employee performance, incentives on motivation, motivation on employee performance, and incentives through motivation on employee performance, shows a significant effect with a T-Statistic of more than 1,96 and a P-Value of less than 0,05. the results of this study are expected to provide insight into the effect of motivation and compensation on employee performance.WordsCharactersReading time